THE RESPONSIBILITY TO PROTECT IN NORMATIVE DEADLOCK: ASEAN’S DILEMMA IN THE ROHINGYA ISSUE - Adli Hazmi; Meltem YIlmaz; Idham Badruzaman (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2025)
This article examines the limitations of the Responsibility to Protect (R2P) in Southeast Asia, using the Rohingya crisis in Myanmar as a case study. While ASEAN has formally endorsed R2P, its response to the crisis reveals a persistent gap between normative commitment and institutional capacity. This study investigates how deeply entrenched principles of non-interference and consensus have shaped ASEAN’s reluctance to operationalise protective norms, even amid documented mass atrocities. Drawing on qualitative document analysis and framed within constructivist and norm localisation theories, the article explores both regional and global failures to act. The analysis reveals that ASEAN’s response was fragmented, with individual member states selectively engaging based on domestic interests, and that international inaction further eroded the credibility of R2P. By highlighting the disjuncture between rhetorical acceptance and practical implementation, the article argues for a reinterpretation of sovereignty and a rethinking of institutional mechanisms in order to strengthen atrocity prevention in the region. The study further recommends that ASEAN develop a regional monitoring and early-warning mechanism to enhance timely and coordinated responses to emerging mass-atrocity risks.